Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-70 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
The arching of the back is impaired in the patient Nefeli (A). In the four-year-old brother the arch of the back is physiologic (B).